China in the twenty-first century : politics, economy, and society (United Nations University Press, 1997)
China has experienced tremendous change during the era of the People's Republic, particularly during the past 15 years, a period in which it has begun a shift from a centrally planned economy to a market-oriented system. This book, based on an international symposium held at Aoyama Gakuin University, Tokyo, attempts to form a picture of the landscape of China in the twenty-first century.